2006
DOI: 10.3354/meps325181
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent temporal patterns in light absorbance and fish abundance

Abstract: The abundance of midwater fishes in fjord basins, as well as the abundance and size of mesozooplankton, have previously been related to optical properties of the basin water. Herein, we report on concurrent temporal changes in light absorbance and fish abundance for Masfjorden and modest changes in both variables for Lurefjorden and Sognefjorden, western Norway. The inverse relationship between fish abundance and absorbance in the temporal data, spanning 9 yr, is consistent with the relationship previously des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
(25 reference statements)
0
15
0
Order By: Relevance
“…Thus to optimise their fitness zooplankton have to choose the optimal vertical position in the water column by balancing feeding conditions against predation risk. Several recent studies suggest that optical properties are important in shaping abundances and vertical distributions in plankton and fish populations (Aksnes et al 2004, Sørnes and Aksnes 2006, Sørnes et al 2007, Aksnes 2007. I observed a positive linear relationship between the vertical range of the depth distribution and the mean depth for the copepodite stages of C. finmarchicus and M. longa (paper III).…”
Section: Vertical Distribution and Migrationmentioning
confidence: 86%
“…Thus to optimise their fitness zooplankton have to choose the optimal vertical position in the water column by balancing feeding conditions against predation risk. Several recent studies suggest that optical properties are important in shaping abundances and vertical distributions in plankton and fish populations (Aksnes et al 2004, Sørnes and Aksnes 2006, Sørnes et al 2007, Aksnes 2007. I observed a positive linear relationship between the vertical range of the depth distribution and the mean depth for the copepodite stages of C. finmarchicus and M. longa (paper III).…”
Section: Vertical Distribution and Migrationmentioning
confidence: 86%
“…The size effect on light attenuation is secondary to concentration, but size is important in determining the flux of nutrient and light into phytoplankton cells and, hence, provides a physical constraint on their growth rate (Finkel & Irwin 2000, Karp-Boss et al 1996. Available light for visual predators may affect trophic interactions in the sea, as it has been proposed as an explanation for the shift between zooplanktonivorous fishes and jellyfish in the northern European seas (Aksnes et al 2004, Sornes & Aksnes 2006, Sornes et al 2008. Therefore, measuring PSD and knowing the particle properties (see Figure 5) to infer light attenuation in the water column of different particle size classes may be helpful in understanding changes in the pelagic ecosystem.…”
Section: Size Effects On the Food Web And Vertical Fluxesmentioning
confidence: 99%
“…Jellyfish are highly opportunistic because they are less sensitive to hypoxia compared to fishes and crustaceans (Vaquer-Sunyer and Duarte, 2008), warmer temperatures enhance jellyfish reproduction (Purcell et al, 2007;Purcell, 2012), and overfishing enhances prey availability and reduces competition pressure for jellyfish (Lynam et al, 2006). Eutrophication also benefits tactile predators like jellyfish by increasing water-column turbidity, whereas visual predators (e.g., fish) are at a competitive disadvantage compared to jellyfish in this situation (Sørnes and Aksnes, 2006;Sørnes et al, 2007;Aksnes et al, 2009). While recent meta-analyses have shown that global jellyfish populations have only increased slightly since the 1970s (Condon et al, 2012), numerous areas throughout the world have experienced large jellyfish population expansions (Lynam et al, 2006;Purcell, 2012).…”
Section: Introductionmentioning
confidence: 99%